“Getting Better”: The Politics of Comparison in Addiction Treatment and Research - Fraser, Suzanne; Ekendahl, M. (Federal Legal Publications, Inc, 2018)
© 2018, The Author(s) 2018. The alcohol and other drug field is characterized by great diversity in kinds of treatment and treatment philosophies. Even the kinds of problems treatment is expected to address vary significantly, although agreement seems to exist that the general purpose is to help people “get better.” This article considers this diversity, drawing on a qualitative project conducted in three countries: Australia, Canada, and Sweden. Inspired by the project’s multisite approach and the questions it raises about comparative research, the article critically engages with the notion of “comparison” to think through what is at stake in making comparisons. Analyzing 80 interviews conducted with policy makers, service providers, and peer advocates, the article maps key ways treatment is conceptualized, identifying in them a central role for comparison. Participants in all sites invoked the need to consider addiction a multifaceted problem requiring a mix of responses tailored to individual differences. Related notions of “holism” were also commonly invoked, as was the need to concentrate on overall improvements in well-being rather than narrow changes in consumption patterns. In conducting this analysis, this article poses a series of critical questions. What kinds of comparisons about quality of life, the self, and well-being do treatments for addiction put into play? What categories and criteria of comparison are naturalized in these processes? What kinds of insights might these categories and criteria authorize, and what might they rule out? In short, what does it mean to understand alcohol and other drug use and our responses to it as intimately intertwined with the need to “get better,” and what happens when we scrutinize the politics of comparison at work in getting better through addiction treatment? We conclude by arguing for the need to find new, fairer, ways of constituting the problems we presently ascribe to drugs and addiction.